1 Understanding aims, successes and challenges of palliative care and homelessness projects across the UK. (30th January 2023) - Crooks, Jodie; Shulman, Caroline; Flemming, Kate; Shaw, Emma; Hudson, Briony
Abstract : Introduction: Across the UK there are a growing number of projects, aiming to improve care for people experiencing homelessness (PEH) with advanced ill health. There has been no centralised place for professionals to share experiences, learn from each other and collaborate. Aims: To understand the current landscape within the field of palliative care and homelessness in the UK, by exploring existing project aims, successes and challenges. Methods: An Extension for Community Healthcare Outcomes (ECHO) network was established as a virtual community of practice to bring together a range of professionals with an interest or project in palliative care and homelessness. An online survey was distributed to the network to explore the aims, successes and challenges of palliative care and homelessness projects. Responses were summarised using descriptive statistics and free text responses were analysed using thematic analysis. Results: To date the ECHO sessions have been well attended, each averaging 72 professionals. 153 responses to the survey were completed. Projects focussed on service delivery (56%) training (20%) and research (19%). Themes for success included: improved service engagement; relationship formation; housing provision; honouring EOL wishes; upskilling staff and enabling safe hospital discharge. Main challenges included: stigma around substance misuse; securing funding; staff capacity; equipment and facilities; and engaging communities. Conclusions: This survey mapped projects aiming to improve care and support for PEH with advanced ill health and identified successes and challenges. The ECHO network provides a forum for knowledge exchange, pooling expertise and resources. Impact: This project has facilitated valuable connections between people working to improve support for PEH with advanced ill health. It has also enabled UK-wide mapping of projects and the development of partnerships to strengthen research, understanding and improvements.